Circulation book use of the U.P. College of Home Economics Library with implications to collection development - Pangilinan,Judith M.; Gonzales, Grace Marie B.; Lapuz, Elvira B.; Mallari, Florenda D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The Circulation book collection of the UP College of Home Economics Library was evaluated to determine the book usage statistics and the book borrowing patterns of students starting from Second semester AY 2004-2005 up to the First semester AY 2005-2006, including Summer of 2006. The shelf list, book card and the OPAC were used to gather the data needed in the study.
The results of the study were used to evaluate the collection development of the CHE Library. Almost 75 of the total collection were circulation books. It was the FSN Department which had the most number of undergraduate enrollees while the FLCD had the most number of graduate enrollees. In terms of book allocation, FSN Department got the highest allocation of books with 20.6 while the HEEd Department had the lowest book allocation with only 6.6 of the total collections. The heavy users of the circulation books in the CHE Library were the students, specifically the undergraduate students. It was also the FSN Department, which had the highest (1,170) book loans while the HEEd Department got the least (184) book loans.
Results revealed that there were more inactive books than active books in all departments. CTID Department recorded the most number of active books (48.8) while the HEEd Department had the least number active books (23.4). A significant (p0.05) differences in the proportion of active and inactive books existed among the different departments. The most frequently borrowed book was a particular title use both by students from FSN and HRIM Departments. There was a significant (p0.05) relationship between the year of publication and the number of active books.
Results showed that books that were published recently (1991-present) were in great demand. Based on the result of the study, weeding is highly recommended to decrease the numbers of inactive books in the CHE Library. Further strengthening of the Circulation book collection of the CHE Library is also recommended for all departments with special attention given to the HEEd Department. The HEEd Department should be in top priority when purchasing new and up-to-date books. The findings of the study maybe used as guidelines by the librarian in planning, determining and evaluating the Circulation section of the CHE Library.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Circulation analysis -- Philippines -- Quezon City; Academic libraries -- Philippines -- Quezon City -- Use studies; Library use studies -- Philippines -- Quezon City; Academic libraries -- Collection development -- Philippines -- Quezon City